2001
DOI: 10.1115/1.1389464
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Turbulent Heat Transfer in Twisted Square Ducts

Abstract: This paper describes the experimental and numerical study of three mildly twisted square ducts (twisted uniform cross section square duct, twisted divergent square duct and twisted convergent square duct). Experiments are conducted for air with uniform heat flux condition. Measurements are also conducted for a straight untwisted square duct for comparison purpose. Numerical simulations are performed for three-dimensional and fully elliptic flow and heat transfer by using a body-fitted finite volume method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Wang et al [13] Twisted square duct Air 10,000-100,000 The twisting brings about a special variation pattern of the spanwise distribution of the local heat transfer coefficient Sajadi et al [14] Alternating flattened tube Oil 500-2000…”
Section: Continuity Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [13] Twisted square duct Air 10,000-100,000 The twisting brings about a special variation pattern of the spanwise distribution of the local heat transfer coefficient Sajadi et al [14] Alternating flattened tube Oil 500-2000…”
Section: Continuity Equationmentioning
confidence: 99%
“…They also found that twisted square duct performed well in laminar and also to some extent in turbulent flow regime due to strong presence of secondary flow and the maximum enhancements factor of 10.5 was obtained with twist ratio of 2.5, Prandtl number of 20 and Reynolds number of 3000. Wang et al [13] investigated the turbulent heat transfer in twisted square ducts. Their results revealed that the twisted divergent duct always enhanced heat transfer, the twisted convergent duct always deteriorated heat transfer, and the twisted constant cross section duct was somewhat in between.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [40] Three twisted square ducts were studied for experimental and numerical analysis (twisted uniform, twisted divergent, and twisted convergent )for the square duct. The experimental and theoretical findings show that the span-wise distribution of the local heat transfer coefficient varies uniquely due to twisting, whereas the axial distribution varies for convergent and divergent geometries.…”
Section: Mahato Et Al[36] Examined the Gnielinski Andmentioning
confidence: 99%
“…The TT is usually made of metallic material, with proper dimensioning. TT is also considered the eddy generator that enhances the HT coefficient [ [14] , [15] , [16] , [17] , [18] ]. The goal of the current study is to provide the necessary information of twisted tape geometry fixed in the tube for the thermal enhancement of the system [ [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%